Análisis multitemporal de la expansión minera en los páramos de la comunidad San Agustín de Callo perteneciente a la parroquia Mulaló periodo 2015 – 2023. - Toapanta Gagñay, Brayan Paul (2024)
This study presents the multi-temporal analysis of mining expansion in the San Agustín de Callo community belonging to the Mulaló parish, Cotopaxi province. The community, like other sectors of the Andean moor, has experienced modifications in land use based on the increase of mining activity. Therefore, the main objective of this research is to determine the progress of mining activity by calculating the change in land use photointerpreted in the satellite images corresponding to the period 2015 – 2023. In turn, by applying a survey it is understood the perception of the local community regarding changes in vegetation cover and mining activity. For its development, a quantitative and qualitative methodology was applied through the following methodological process: (1) selection and obtaining of satellite images from the Google Earth Pro platform (years 2015, 2017, 2022 and 2023), (2) georeferencing of images satellite images, (3) photointerpretation of intervention areas due to mining activity, (4) validation of photointerpretation, (5) multi-temporal analysis of mining activity polygons, (6) formulation and application of survey. This process resulted in the identification of 57 mining exploitation polygons in the periods from 2015 to 2023, which through multi-temporal analysis allowed the comparison of progress or cessation of mining activity between years. Thus, taking as a reference the analysis of land use and coverage corresponding to the year 2015, it was observed that there were 10 mining points, while, for the year 2017, they increased to 16. Subsequently, for the year 2022, an increase to 20 was quantified. mining points, and by 2023 the reduction of mining exploitation to 11 points is observed. It is concluded that the moor has been modified over the years, with the loss of biodiversity being more evident in the first four years of analysis due to the gradual increase in mining activity, while by 2023 there was a slight reduction in mining areas due to the control carried out by the entities in charge. This has been achieved thanks to the management that the community has carried out day after day for their well-being and at the same time to preserve the moors of the surrounding sectors.